Pratique # 21 : ConnectAînés / Francsavoir (pancanadienne) - Benoît, Josée; Michel, Jean Nephetaly (2021)

Pratique # 22 : Bien vieillir chez soi / Soutien à domicile (pancanadienne) - Benoît, Josée; Michel, Jean Nephetaly (2021)

Public policy and citizen-based practices that support social and health services for official and co-official language minority communities. An international perspective: What has really been achieved and what are the gaps | Politiques publiques et pratiques citoyennes soutenant les services sociaux et de santé pour les communautés minoritaires de langue officielle et coofficielles. Une perspective internationale : ce qui a été accompli et ce qui reste à faire - Bouchard, Louise; Nyqvist, Fredrica; Mari Mayans, Isidor; van Kemenade, Solange; Maisonneuve, Alexander. R. (Linguistic Minorities and Society / Minorités linguistiques et société, 2021)

The principle of minority protection and language rights in Canada: The secession reference’s legacy - Chouinard, Stéphanie (Journal of Parliamentary and Political Law, 2021)

Loi sur les langues officielles et vitalité des minorités : mission impossible ou oeuvre inachevée ? - Landry, Rodrigue (Minorités linguistiques et société, 2021)
Notre article vise à déterminer les conditions nécessaires pour qu’une loi et des politiques linguistiques puissent avoir un effet réel sur la vitalité d’une minorité. L’article comprend trois parties. Premièrement, nous concluons que la Loi sur les langues officielles (LLO) a eu peu d’effet sur la vitalité des minorités de langue officielle. En deuxième partie, nous distinguons trois acteurs essentiels qui agissent sur la vitalité linguistique : la communauté d’intimité, la société civile de la minorité et l’État. De ces analyses, nous dégageons deux principes sociolinguistiques que toute législation linguistique devrait respecter si son objet est de favoriser la vitalité/revitalisation d’une minorité. Enfin, nous focalisons sur la partie VII de la LLO, la plus susceptible de favoriser la mise en oeuvre d’un aménagement linguistique planifié et global capable de respecter les deux principes sociolinguistiques, de coordonner une synergie d’action des acteurs essentiels et d’avoir un effet réel sur la vitalité des minorités. Mots-clés : Loi sur les langues officielles, vitalité ethnolinguistique, autonomie culturelle, aménagement linguistique, politiques linguistiques, droits linguistiques

Improving access to health services in French: The power of networking and knowledge mobilization, a proven Canadian Model - Tremblay, Michel; Leis, Anne (Linguistic Minorities and Society, 2021)
Language barriers have a detrimental impact on access to health services and compromise patients’ safety. The purpose of this article is to describe and evaluate how the Société Santé en français (SSF) and the 16 French Language Health (FLH) networks used networking and knowledge mobilization for improving access to health services in French for Francophone and Acadian minority communities (FAMC). Method: Data was extracted from the 2013-2018 program’s reports and evaluation. Results confirmed that networking effectively mobilized key partners for better access to health services in French regardless of location. This access increased incrementally as a function of the customized level of support provided to the system by the SSF and the FLH networks and, to a lesser extent, when FAMC represented over 3.5% of the total population in the region, province or territory. Networking and knowledge mobilization contribute to augmenting access to safe, quality health services in French for FAMC. Keywords: access, partnership and networking, active offer, language barriers, knowledge mobilization